INOVASI PENDIDIKAN NONFORMAL UNTUK PEMBERDAYAAN PEREMPUAN DI DESA KEBONAGUNG: PENDEKATAN DAN OUTPUT PROGRAM SEKOLAH PEREMPUAN - Neysa Hanifa, Shaina; Marsyal Arijanto, Raihan; Badar Anugrah Illahi, Muhammad (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Women's empowerment is a key element in achieving sustainable development, especially amidst global challenges such as gender inequality and limited access to education and economic resources. Kebonagung Village, located in Imogiri Subdistrict, Bantul Regency, DI Yogyakarta, has significant potential in its cultural and natural resources. However, women in this village still face various challenges in maximizing their roles as leaders and drivers of local development. A survey conducted by the Student Executive Board of the Faculty of Social and Political Sciences at Universitas Muhammadiyah Yogyakarta revealed that the majority of women in Kebonagung Village are still hindered in accessing life skills and gender equality, with the workforce being male-dominated and limited opportunities for women to enhance their skills. To address these issues, the Sekolah Srikandi Program was designed as a strategic initiative to empower women in Kebonagung Village through structured and sustainable non-formal education. This program involves the village government, local community, and other stakeholders, focusing on enhancing women's capacities in various aspects of life, including safety, family management, roles in village development, as well as mastery of information technology and access to economic and natural resources. With the collaboration of local women's organizations such as Desa Prima Mandiri and PKK, the Sekolah Srikandi Program aims to develop women's skills and knowledge so that they can improve their quality of life, actively contribute to village development, and become increasingly independent and empowered in various aspects of life.